The shimmer - Morrell, David. 1943- (Vanguard Press, 2009)
Santa Fe police officer Dan Page tracks down his missing wife only to witness a bloodbath in Rostov, a remote town in Texas famous for a massive astronomical observatory, a long-abandoned military base, and unexplained nighttime phenomena that draw onlookers from every corner of the globe. Determined to solve the mystery of the Rostov Lights in order to save his wife, he discovers that the decaying military base may not be abandoned at all, and that the government may have known about the lights for decades--and the unimaginable danger behind them.